Correlation and path coefficient studies for yield and its components of upland rice (Oryza sativa L.) in North Western Ethiopia - Belete, Desta Abebe; Tewachew , Atsedemariam; Bitew, Mulugeta; Mulualem, Tafere (Journal of Scientific Agriculture, 2022)
Rice is the major source of calories and third largest crop after maize and wheat by productivity. The aim of the present study was to determine the correlations between grain yield and its contributing traits and to measure the direct and indirect effects of those traits on grain yield in upland rice. Sixteen upland rice genotypes were tested using RCBD with three replications at Pawe district (on station and on farm) during 2016/2017 main cropping season. The estimates of genotypic and phenotypic correlation coefficients between nine characters were computed and also the direct and indirect effects. The results obtained indicated that estimates of genotypic correlation coefficients between nine characters were generally different in sign but higher in magnitude than the corresponding phenotypic correlation coefficients. Days to maturity and plant height were showed strong positive and significant phenotypic and genotypic correlations with days to 50% heading at on farm level. Whereas, thousand seed weight was exhibited strong positive and significant phenotypic and genotypic correlations with days to 50% heading followed by panicle length at on station level. The highest positive both phenotypic and genotypic direct effect on grain yield were exerted by days to heading followed by panicle length and number of filled grain per panicle. In contrast, high order of negative both phenotypic and genotypic indirect effects were extended by panicle length on grain yield via days to maturity (-0.167), thousand seed weight (-0.162) and plant height (-0.09). The direct effects of the remaining six characters were too low to be considered important and the rest of the estimates of indirect effects obtained in path analysis were negligible. Generally, it can be concluded that there is a favorable situation for obtaining high response to selection in improving yield and its components in upland rice.